Comparison of channelled videolaryngoscope and intubating laryngeal mask airway for tracheal intubation in obese patients: a randomised clinical trial - Turna,Canan Kamile (2020)
Abstract Background: Obesity causes various difficulties in intubation and ventilation, which are confronted due to increased fat tissue in the upper airway and diminished compliance in the chest wall. Videolaryngoscopes and Intubating Laryngeal Mask Airway (ILMA) are good options as recommended by the American Society of Anesthesologists (ASA) difficult airway guidelines. We aimed to compare ILMA and Airtraq (a channeled videolaryngoscope) in obese patients. Methods: Eighty patients with ASA physical status 1-3, aged between 18 and 65 years and with a body mass index greater than 35 kg.m-2, who were undergoing elective surgery requiring orotracheal intubation, were included in the study. Patients were intubated with one of the devices cited. Results: There was no difference between the number of intubation attempts, insertion times and need for optimisation manoeuvres of Airtraq and ILMA. The intubation with Airtraq was accomplished in a shorter period of time than in that in the ILMA group (29.9 ± 22.1s vs. 50.7 ± 21.2s; p < 0.001). A significant difference was found when the times of total intubation were compared (29.9 ± 22.1s vs. 97.4 ± 42.7s; p < 0.001). The mean arterial pressure statistically increased after device insertion in the ILMA group (p < 0.05). Conclusions: Airtraq appears to be superior to ILMA in obese patients, with a total of time intubation of less than 60 seconds and with low mean arterial pressure changes. However, ILMA is still a useful tool that provides both ventilation and intubation throughout the whole intubation process.